Popular organization and subjectivity: sewing meanings with the youth of a community of Fundo de Pasto (Research, Society and Development, 2020)
The study had like objective understand of meanings of young  people in the process of popular organization in a traditional community of Fundo de Pasto.  The experience access occurred through participant observation with register in the field diary. The analyze of the dices followed way phenomenological indicated by Amatuzzi (1966): a) syntonizing the lived whole; b) meeting the experiential elements of this whole; and c) Perform a synthesis of the experience. From that path, it was identified that the emerged senses are strongly directed to a feeling of belonging to the land and collectivity values, leading to the comprehension of a way of being in the world, muted and threatened. It is pointed out that it is in dialectical interaction between subjectivities and social questions that the potentiation of popular organization occurs, leading young people to greater critical involvement with themselves and their reality. Given this, there is the challenge, the provocation and the possibility of a psychology performance that problematizes and questions the structures that violate peoples subjectivities.